2019
DOI: 10.3390/foods8030109
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Biogenic Amines in Pa (Green Onion) Kimchi and Gat (Mustard Leaf) Kimchi

Abstract: In this study, biogenic amine content in Pa (green onion) kimchi and Gat (mustard leaf) kimchi, Korean specialty kimchi types, was determined by high-performance liquid chromatography (HPLC). Many kimchi samples contained low levels of biogenic amines, but some samples had histamine and tyramine content over the safe levels. Based on the comparative analysis between the ingredient information on food labels and biogenic amine content of kimchi samples, Myeolchi-aekjeot appeared to be an important source of bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…However, spontaneous fermentation may not be an authentic system to obtain a safe and palatable final product as the possibility of detrimental microbiological/toxicological consequences such as biogenic amines, mycotoxins, and pathogenic microbes, could not be excluded [ 15 ]. Recently, Lee et al [ 16 ] indicated the involvement of autochthonous LAB in biogenic amine accumulation during spontaneous fermentation of green onion kimchi. Although thermal treatments are effective in the elimination of autochthonous microorganisms and endogenous enzymes from plant matrices, they irreversibly deteriorate the associated biofunctionalities through altering the chemical composition [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, spontaneous fermentation may not be an authentic system to obtain a safe and palatable final product as the possibility of detrimental microbiological/toxicological consequences such as biogenic amines, mycotoxins, and pathogenic microbes, could not be excluded [ 15 ]. Recently, Lee et al [ 16 ] indicated the involvement of autochthonous LAB in biogenic amine accumulation during spontaneous fermentation of green onion kimchi. Although thermal treatments are effective in the elimination of autochthonous microorganisms and endogenous enzymes from plant matrices, they irreversibly deteriorate the associated biofunctionalities through altering the chemical composition [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to dairy-based food fermentations, fermentations that use plant materials as the main substrate are little explored, except for a few examples such as kimchi (fermented with Chinese mustard), sauerkraut (fermented with cabbage) and pickles and can be interesting to lactose intolerants, to people allergic to milk or to vegans [45]. In kimchi samples collected on the Korean market, histamine and tyramine content above safe levels were found ( Table 1) [53]. Sauerkraut is one of the best known and most commercialized traditional vegetable foods in Europe.…”
Section: Fermented Food and Beverages And Their Bioactive Amines Agaimentioning
confidence: 99%
“…Tyramine content in Chonggak kimchi as reported by Kang et al [26] were at safe concentrations, while Mah et al [29] reported safe concentrations of both histamine and tyramine below recommended limits. As for Gat kimchi (mustard leaf kimchi), Lee et al [31] reported histamine concentrations which exceeded the recommended limit by a factor of 2, while tyramine content slightly exceeded the limit. In contrast, Mah et al [29] reported that Gat kimchi did not contain histamine and tyramine at detectable levels.…”
Section: Biogenic Amine Content In Kimchi Productsmentioning
confidence: 99%
“…Similarly, Kang et al [26] also reported tyramine concentrations in Kkakdugi below the recommended limit. As for Pa kimchi (green onion kimchi), Lee et al [31] reported histamine and tyramine concentrations exceeded recommended limits by a factor of 4 and 2, respectively. In contrast, Mah et al [29] reported histamine and tyramine in Pa kimchi at safe concentrations as tyramine content was not detected while histamine content remained below 30 mg/kg.…”
Section: Biogenic Amine Content In Kimchi Productsmentioning
confidence: 99%
See 1 more Smart Citation